APPLICATION OF MULTI-CRITERIA DECISION ANALYSIS TO SUPPORT LAND USE DECISION-MAKING IN ANKASA CONSERVATION AREA, GHANA - Lawrence DAMNYAG; Francis TEASE; Alex Aboagye BAMPOH; Jewel ANDOH (Journal of Applied Life Sciences and Environment, 2023)
Deforestation in Ghana is primarily caused by agriculture, and as such, there is a need to explore agricultural systems that promote forest and environmental conservation. Studies on decision support frameworks that can help farmers and landowners make informed optimal land use choices are limited in the country. This study attempts to fill the gap. We used survey questionnaire and focus group discussion to gather data from farmers and other stakeholders. Multi-Criteria Decision Analysis (MCDA) technique was employed to analyse the data. The results showed that agroforestry, with the highest ranking (probability of 0.98), is the optimal land use option. Coconut and oil palm land use options were perceived to be contributing to the degradation of the periphery of the Ankasa Conservation Area (ACA). Intensifying education and training will increase the uptake of agroforestry as an integrated multifunctional land use strategy in the ACA.